The Role Of The Indonesian National Armed Forces In World Peace Operations - Ryanda Catur Arhanudya; Syaiful Anwar; Rizerius Eko Hadisancoko; Guruh Prabowo Wirajati; Priyanto, Priyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Indonesian National Armed Forces in world peacekeeping operations are part of Indonesia's commitment to global stability. Through a qualitative analysis approach, this research provides a holistic overview of the contribution of the Indonesian National Armed Forces in the context of maintaining order and security, providing humanitarian assistance, and training and developing local capacities. A critical role is played in upholding ceasefires and engaging in the enforcement of international rules and laws in various conflict regions. The presence of the Indonesian National Armed Forces helps create a secure environment for the peace process, offering protection to civilians, and overseeing the compliance of parties involved in the conflict. Actively involved in humanitarian assistance, sending food, medicine, and medical support to conflict-affected areas. These humanitarian efforts demonstrate the positive role of the Indonesian National Armed Forces in responding to humanitarian crises and assisting communities in need, creating a direct and positive impact on civilians. The participation of the Indonesian National Armed Forces in world peacekeeping operations not only reflects Indonesia's responsibility for global peace but also illustrates concrete efforts to be a positive force in conflict resolution and post-conflict community development. The implications of these findings can assist in designing more effective policies to support the role of the Indonesian National Armed Forces in maintaining peace and stability at the international level.